Innowacje w kolokacjach w Wojnie polsko-ruskiej pod flagą biało-czerwoną Doroty Masłowskiej i ich tłumaczenie na język rosyjski - Orzechowska, Joanna (Acta Polono-Ruthenica, 2018)
The paper presents the phenomenon of extended collocations in the novel Wojna polsko-ruska pod flagą biało-czerwoną by Dorota Masłowska. Innovative collocations are analysed with reference to an adverb ‘doszczętnie’ [Eng. thoroughly]. New unconventional collocations are among the factors thanks to which the language of the novel is believed to have undergone deconstruction. Unfortunately, in the Russian version of the novel the translator did not reflect the discussed phenomenon, which deprived Russian readers of part of the aesthetic linguistic experience available to Polish readers.